The financing pharmaceutical assistance in a border municipality: Survey of medicine consumption during the SARS-CoV-2 pandemic (Research, Society and Development, 2022)
Both medical care and drug dispensing have no cost in the Unified Health System (SUS), so the presence of immigrants of Paraguayan origin in Foz do Iguaçu is a very present reality, where a large part seeks care in Brazil due to a absence of free services in Paraguay. However, the care of foreigners overloads the distribution of drugs, since the number of patients treated exceeds expectations, even at the time of purchase of medicines. For the development of the research, a study was carried out in the main databases in the field of health related to the topic and data collection regarding the consumption of medicines in the months in which the Border between Brazil and Paraguay was closed due to the Covid-19 pandemic. 19, as well as a report from the previous and following year (2019, 2020 and 2021) through analysis of the Quarterly Accountability Report (RDQ) of the Municipality of Foz do Iguaçu. According to the data obtained during the study, it is possible to observe that the Municipality has a higher than expected pharmaceutical service, this demand makes the public budget for the purchase of medicines insufficient, since the service of foreigners is not included in the transfer of funds. It is also clear that the municipalities bordering Foz do Iguaçu are experiencing structural problems, which do not support the service to their native population, which corroborates the overload of care in public pharmacies.